2022
DOI: 10.1039/d2ra02181a
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultralong and photoactive Bi2Ti4O11/TiO2 heterojunction nanofibers toward efficient textile wastewater treatment

Abstract: The elimination of dyes from textile wastewater with a lower carbon footprint is highly contingent on the design of green catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Among them, semiconductor-based photocatalysis has become a research hotspot in water environment treatment due to its sustainable, eco-friendly and low-cost characteristics. 9–11 To date, multitudinous semiconductors have been developed, and typically, semiconducting metallic oxides such as TiO 2 , 12 ZnO 13 and SnO 2 , 14 are extensively researched because of their excellent physical and chemical properties. Nevertheless, due to their wide band gap energies, the effective light response is normally restrained to the ultraviolet region, making them less active under visible-light.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, semiconductor-based photocatalysis has become a research hotspot in water environment treatment due to its sustainable, eco-friendly and low-cost characteristics. 9–11 To date, multitudinous semiconductors have been developed, and typically, semiconducting metallic oxides such as TiO 2 , 12 ZnO 13 and SnO 2 , 14 are extensively researched because of their excellent physical and chemical properties. Nevertheless, due to their wide band gap energies, the effective light response is normally restrained to the ultraviolet region, making them less active under visible-light.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors [ 30 , 31 , 32 , 33 , 34 , 35 ] reported a number of compounds based on the TiO 2 -Bi 2 O 3 system, which exhibit photocatalytic activity in the near-UV and visible range of the spectrum. Bismuth titanates of various compositions can be more effective as photocatalytic materials than that of TiO 2 because of their narrower band gap energy: TiO 2 -based photocatalysts are active only under UV irradiation with λ > 382 nm, while for bismuth titanate-based compounds, the activity can be achieved in the visible spectra range: for Bi 2 Ti 4 O 11 , λ > 400 nm, for Bi 12 TiO 20 , λ > 427 nm, for Bi 2 Ti 2 O 7 , λ > 496 nm, and for Bi 4 Ti 3 O 12 , λ > 421 nm.…”
Section: Introductionmentioning
confidence: 99%